ANALISIS TINGKAT KEPUASAN PELANGGAN JASA PENGISIAN ANGIN DAN POMPA BAN MENGGUNAKAN GAS NITROGEN DI CV AMS - Anggia Arista (Universitas Putera Batam, 2022)
Recently, the filling of vehicle tires, be it cars or motorbikes, has begun to use nitrogen gas as an ingredient for tire pumps. Compared to filling using conventional air media, there are many advantages when consumers or vehicle users fill tire pressure with nitrogen. This is where the distribution of pump outlets and tire fillings using nitrogen began, which are mostly opened at refueling sites or gas stations. This research was conducted at one of the CV business entities in the city of Batam which is engaged in filling and patching tires using nitrogen gas which is located in the Sekupang gas station area which is an industrial area and is close to community services making Sekupang gas stations a strategic area in this line of business. In the service related to filling and patching tires with nitrogen gas, there must be some opinions, both positive and negative, about the service at the outlet. From here, researchers will examine the level of customer satisfaction for filling and filling tires using nitrogen gas. The results of the study are that for the tangible dimension all statements have a satisfied category because the quality value is positive, for the reliability dimension there is 1 attribute that has a negative value, namely statement no 6 with a value of -1.1. For the responsiveness dimension, there is 1 attribute that is dissatisfied with a value of -0.39, namely in statement no. 9. For the assurance dimension there is 1 attribute that has a negative value, namely statement no. 13 with a value of -1.06, while for the empathy dimension there is 1 attribute that is dissatisfied. namely statement no. 15 with a value of -0.56.